Varicella vaccination as useful strategy for reducing the risk of varicella-related hospitalizations in both vaccinated and unvaccinated cohorts (Italy, 2003–2018). Issue 35 (31st July 2020) - Amodio, Emanuele; Casuccio, Alessandra; Tramuto, Fabio; Costantino, Claudio; Marrella, Alessandro; Maida, Carmelo Massimo; Vitale, Francesco; Restivo, Vincenzo
Abstract: Introduction: The present study summarizes evidences of the impact that varicella vaccination (VV) introduction and coverage can have on varicella attributable hospitalization rates. Methods: A retrospective observational study was carried out by considering hospital discharge records and VV coverage at 24 months collected from 2003 to 2018 by the Italian Ministry of Health. All hospitalizations records reporting an ICD-9 CM 052.X code as the principal diagnosis or any of the five secondary diagnoses were considered as related to varicella. The hospitalization rate reduction was evaluated by calculating average annual percent change (AAPC) through joint-point analysis. Results: Hospitalization rates showed a decreasing trend by age: children <1 year of age were the most affected group in each Italian administrative region (42.5/100, 000 per year), whereas lower incidence rates were found in older age groups (23.8/100, 000 in 1–5 years old and <4.0/100, 000 in the following groups). Varicella hospitalization rates decreased significantly after the introduction of VV (3.4 vs. 2.7 per 100, 000; p  < 0.001). During the first five years after the introduction of vaccination, hospitalization rates showed a statistically significant decrease especially among infants <1 year of age (AAPC −35.0%; p  < 0.001) and 1–5 years old (AAPC −35.2%; p  < 0.01). Total percentage changes were −80.0% and −86.7%, in the age class <1 year old and 1–5 years old, respectively. Conclusions: All the previously reported findings confirm that hospitalization rates are strictly related to both the vaccination coverage and the number of years since the introduction of the vaccination. VV confirms to be an important step in public health strategies and the introduction of universal vaccination, with high vaccination coverage, should be considered as an extremely powerful tool to reduce the risk of complications.